Effect of the lambda S gene product on properties of the Escherichia coli inner membrane. - Wilson, D B (1982)
The S gene of bacteriophage lambda is a late gene required for cell lysis, but unlike the other two lysis genes, R and Rz, it does not code for an endolysin. Earlier studies have shown that the S gene product inhibits respiration and macromolecular synthesis and makes the inner membrane permeable to sucrose. In this study, the effect of the S gene product on a number of Escherichia coli membrane functions (active transport, permeability, respiration, and transhydrogenase and ATPase activity) were measured, and a product of the lambda S gene was identified in the inner membrane fraction by two-dimensional polyacrylamide gel electrophoresis. The results of these experiments indicate that the lambda S product is present in the inner membrane, that it increased the permeability of the membrane for all of the small molecules that were tested, and that its action is reversible. The simplest explanation of these results is that the S gene product forms a hydrophilic pore through the inner membrane, allowing small molecules and lambda lysozyme to pass through.